Effect of Figure Eight Vision Exercise Combined with Chin Nodding and Neck Stretching Exercises on Computer Vision Syndrome - Maryam Basharat, Fareeha Shakeel, Tahira Rubab, Mahnoor Fatima, Ibraheem Zafar, Amna Ahsan, Ramsha Masood, Muhammad Saad Shafique (Pakistan Journal of Medical & Health Sciences, 2023)
Purpose: Main aim of the study is to evaluate the effectiveness of vision exercise with chin nodding and neck stretching among computer users and also intend to show the effect of figure eight vision exercise only. Methods: This randomized controlled trial study was carried out among computer users in Islamabad and Rawalpindi. Computer vision syndrome symptoms data will be collected from self-administered questionnaire and computer vision syndrome level instrument questionnaire. 33 participants (17=male, 16=female) in group A (experimental group) will be given figure eight vision exercise and chin nodding and neck stretching. 33 participants (17=male, 16=female) in group B (control group) will be given only figure eight vision exercise with one month follow up. Intervention will be given 4 to 5 times per week (once in a day). Data analysis will be done through SPSS. Results: In both the questionnaires, in between the groups, pre and post intervention P value shows non-significant results. While within groups, in questionnaire 1, pre and post intervention P-value was 0.00 which shows significant results and in questionnaire 2, P-value of group A was 0.02 which shows significant results while in group B, P-value was 0.13 which shows non-significant results. Practical Implication: Regarding comparison of exercises difference between group A and B was non- significant. But, in within groups, in self-administered questionnaire both groups’ shows significant results individually while in CVS level instrument questionnaire, group A shows significant result and group B shows non-significant Conclusion: Study concludes that both groups showed non-significant results regarding comparison of exercises but in within groups, in self-administered questionnaire both groups’ shows significant results individually while in CVS level instrument questionnaire, group A shows significant result and group B shows non-significant. Keywords: Randomized controlled trial, computer vision syndrome, vision exercise, neck stretching (exercise therapy).